PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS KETIDAKSESUAIAN BARANG DENGAN DESKRIPSI DALAM TRANSAKSI E-COMMERCE DI INDONESIA - Kian Fung; Poltak Maruli Immanuel; Deni Firwandi; Tonizar Lumbanbatu; Paltiada Saragi (Honeste Vivere, 2026)
The development of electronic commerce has shifted consumer transactions from conventional markets to digital markets characterized by the absence of physical encounters between the parties and the consumer's dependence on information presented by business actors. This characteristic creates an information asymmetry that places consumers in a weak bargaining position, manifested, among others, in the receipt of goods that do not conform to their description. This study examines two issues: the forms of legal protection available to consumers who receive non-conforming goods in e-commerce transactions, and the construction of business actors' liability for consumer losses. Employing normative legal research with statutory and conceptual approaches, the study finds that legal protection is available preventively through the regulation of the consumer's right to truthful, clear, and honest information together with the obligations and prohibitions imposed on business actors, and repressively through compensation mechanisms and dispute resolution both in and out of court. A product description constitutes part of the contract, so that non-conformity may be construed as a breach of contract, and where misleading information is involved, as an unlawful act. Business actors' liability follows the principle of presumption of liability with a reversed burden of proof, yet remains limited by the principle of balance and the consumer's duty of good faith, rendering such liability proportional rather than absolute.